Respuesta :

Answer:

[tex]a_0 = -6[/tex]

[tex]a_1=8[/tex]

[tex]x^2 +y^2 -6x + 8y = 0[/tex]

Step-by-step explanation:

The equation of the circle has the following form

[tex]x^2 + y^2 + a_0x + a_1y=0[/tex]

The equation of the circle has the following form

We know that the circle goes through the following points

(0, 0)

(6, 0)

(0, -8).

Then we substitute the values of x and y in the equation

For (0, 0)

[tex]0^2 + 0^2 + a_0(0) + a_1(0)=0[/tex]

[tex]0=0[/tex]

For  (6, 0)

[tex]6^2 + 0^2 + a_0(6) + a_1(0)=0[/tex]

[tex]36 + 6a_0=0[/tex]

[tex]a_0 = -\frac{36}{6}\\\\a_0 = -6[/tex]

For (0, -8)

[tex]0^2 + (-8)^2 + a_0(0) + a_1(-8)=0[/tex]

[tex](-8)^2 - 8a_1=0[/tex]

[tex](-8)^2 = 8a_1[/tex]

[tex]a_1=8[/tex]

Finally the equation is:

[tex]x^2 +y^2 -6x + 8y = 0[/tex]

ACCESS MORE